2016
DOI: 10.1371/journal.pone.0161694
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Responses of Soil Respiration and C-Cycle Enzyme Activities to Additions of Biochar and Urea in a Calcareous Soil

Abstract: Biochar (BC) addition to soil is a proposed strategy to enhance soil fertility and crop productivity. However, there is limited knowledge regarding responses of soil respiration and C-cycle enzyme activities to BC and nitrogen (N) additions in a calcareous soil. A 56-day incubation experiment was conducted to investigate the combined effects of BC addition rates (0, 0.5, 1.0, 2.5 and 5.0% by mass) and urea (U) application on soil nutrients, soil respiration and C-cycle enzyme activities in a calcareous soil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
1
4
0
2
Order By: Relevance
“…In this study, though no significant interaction of the biochar and N input appeared, our results showed that the levels of CO 2 in the biochar-amended treatments with N inputs were higher than those in the biochar alone soils and the control (Figure 3) over the short term, which was in agreement with the results reported by Wang et al and Song et al [42,43], who found that the application of biochar combined with N fertilization enhanced CO 2 emissions in the incubation experiments. A significant increase in basal and substrate-induced respiration occurred in the treatments with added biochar combined with mineral fertilization [34,39], which suggested that soil C mineralization would be stimulated in the short term.…”
Section: Biochar Combined With N Fertilization Impact On Soil Co 2 Emsupporting
confidence: 93%
“…In this study, though no significant interaction of the biochar and N input appeared, our results showed that the levels of CO 2 in the biochar-amended treatments with N inputs were higher than those in the biochar alone soils and the control (Figure 3) over the short term, which was in agreement with the results reported by Wang et al and Song et al [42,43], who found that the application of biochar combined with N fertilization enhanced CO 2 emissions in the incubation experiments. A significant increase in basal and substrate-induced respiration occurred in the treatments with added biochar combined with mineral fertilization [34,39], which suggested that soil C mineralization would be stimulated in the short term.…”
Section: Biochar Combined With N Fertilization Impact On Soil Co 2 Emsupporting
confidence: 93%
“…Biochar application can have contrasting effects on soil enzyme activities. For instance, biochar application was found to significantly increase (Pukalchik et al 2018), decrease (Chen et al 2013;Zhang et al 2014;Zheng et al 2016;Benavente et al 2018) or not change (Yoo and Kang 2012;Song et al 2016) β-1,4-glucosidase activities in upland agricultural soils. Similarly, biochar application has been shown to increase (Song et al 2018), decrease (Bamminger et al 2014;Chen et al 2017) or have no effect (Chen et al 2019) on the activities of β-1,4-N-acetylglucosaminidase, which is involved in N-acquiring activities of microorganisms (Parham and Deng 2000).…”
Section: Introductionmentioning
confidence: 98%
“…These enzymes target different groups of substrates present in soils for SOM decomposition (Sinsabaugh 2010) and their activities are substantially influenced by biochar application (Paz-Ferreiro et al 2013;Zhang et al 2014;Song et al 2018). In biochar application studies, the most widely assayed soil hydrolytic enzymes for C cycling (C-acquisition) are β-1,4-glucosidase, β-d-cellobiohydrolase and β-1,4-xylosidase; β-1,4-N-acetylglucosaminidase, leucine amino peptidase and urease for N cycling (N-acquisition); and acid phosphatase and alkaline phosphatase for P cycling (P-acquisition) (Chen et al 2013;Song et al 2016;Pukalchik et al 2018). The phenol oxidase and peroxidase are the most studied oxidizing soil enzymes while dehydrogenase is the most studied intracellular enzyme in biochar application studies (Ouyang et al 2014;Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Одним из перспективных нетрадиционных удобрений является биочар, представляющий собой продукт пиролиза органического вещества, проводимого при температурах от 300 °С до 1000 °С в условиях отсутствия кислорода. Этот материал богат углеродом, характеризуется большой удельной площадью поверхности и обладает высокоароматической структурой [3]. Сырьем для биочара могут служить различные органические отходы: растительный опад, жмых, древесина, осадки сточных вод, отходы животноводства и птицеводства и др.…”
Section: Introductionunclassified
“…Внесение в почву биочара как субстрата, содержащего органогенные элементы, определяет состав и структуру микробных сообществ, вовлеченных во многие процессы, включая трансформацию почвенного органического вещества [3]. Установлено, что различные биочары, в основном полученные из растительных отходов, влияют на метаболическую активность, микробную биомассу, активность почвенных ферментов [14,15].…”
Section: Introductionunclassified